Public Governance and Emerging Technologies: Values, Trust, and Regulatory Compliance (Springer Nature, 2025)
This open access book focuses on public governance’s increasing reliance on emerging digital technologies. ‘Disruptive’ or ‘emerging’ digital technologies, such as artificial intelligence and blockchain, are often portrayed as highly promising, with the potential to transform established societal, economic, or governmental practices. Unsurprisingly, public actors are therefore increasingly experimenting with the application of these emerging digital technologies in public governance. The first part of the book shows how automatization via algorithmic systems, the networked nature of distributed technologies such as blockchain, and data-driven use of AI in public governance can promote hyper-connectivity and hyper-complexity. This trend and the associated concerns have drawn societal, political, and scholarly attention to regulatory compliance considering the current and potential future uses of emerging technologies. Accordingly, the second part of the book focuses on regulatory compliance and regulatory solutions. It explores the compatibility of technology with existing regulations, existing legal tools that could be innovatively applied for the successful regulation of emerging technologies, and approaches to updating existing legislation or creating new legislation for the regulation of emerging technologies. While socio-ethical considerations on upholding public values in a digital world are at the heart of all chapters, the third part specifically focuses on public values and trust. It advances a conceptual, normative discussion, putting the spotlight on trust and other fundamental public values that should be safeguarded. The book shows that the success of using emerging technologies in public governance depends to a large extent on the choices made by key stakeholders in public administration, legislative and regulatory bodies, and tech companies. When using and regulating emerging technologies in public governance, it is crucial to uphold public values and comply with legislation in a way that prioritizes the citizen’s perspective. To this end, the book offers an interdisciplinary approach based on qualitative and conceptual research.